Seroprevalence report on tick-borne encephalitis virus and Crimean-Congo hemorrhagic fever virus among Malaysian’s farm workers - Mohd Shukri, Munirah; Ling Kho, Kai; Ghane Kisomi, Masoumeh; Lani, Rafidah; Marlina, Suria; Muhd Radzi, Siti Fatimah; Tee Tay, Sun; Ping Wong, Li; Awang Mahmud, Awang Bulgiba; Hassan Nizam, Quaza Nizamuddin; Abu Bakar, Sazaly; Zandi, Keivan (BMC public health, 2015)
Tick-borne encephalitis virus (TBEV) and Crimean-Congo haemorrhagic fever virus (CCHFV) are important tick-borne viruses. Despite their wide geographical distribution and ease of acquisition, the prevalence of both viruses in Malaysia is still unknown. This study was conducted to determine the seroprevalence for TBEV and CCHFV among Malaysian farm workers as a high-risk group within the population. We gave questionnaires to 209 farm workers and invited them to participate in the study. Eighty-five agreed to do so. We then collected and tested sera for the presence of anti-TBEV IgG (immunoglobulin G) and anti-CCHFV IgG using a commercial enzyme-linked immunosorbent assay (ELISA) kit. We also tested seroreactive samples against three other related flaviviruses: dengue virus (DENV), West Nile virus (WNV) and Japanese encephalitis virus (JEV) using the ELISA method. The preliminary results showed the presence of anti-TBEV IgG in 31 (36.5%) of 85 sera. However, when testing all the anti-TBEV IgG positive sera against the other three antigenically related flaviviruses to exclude possible cross reactivity, only five (4.2%) sera did not show any cross reactivity. Interestingly, most (70.97%) seropositives subjects mentioned tick-bite experience. However, there was no seroreactive sample for CCHFV. These viruses migrate to neighbouring countries so they should be considered threats for the future, despite the low seroprevalence for TBEV and no serological evidence for CCHFV in this study. Therefore, further investigation involving a large number of human, animal and tick samples that might reveal the viruses' true prevalence is highly recommended.